O Programa Ensino Médio Inovador (ProEMI) e a formação política dos jovens na escola pública - Almeida, Sandra Cristina Andrade Almeida (2016)
The current research aimed at investigating the student’s perceptions on the potentials of the Innovative High School Program (ProEMI) in the political education of young people in a Federal District’s public school. The ProEMI is a strategy from the Ministry of Education (MEC) to improve the quality of high school education through a more dynamic and flexible curriculum. The program has eight macro-fields and the current study is linked to the one of Student Participation. This research’s data were gathered through questionnaires applied in two classes and in a focal group of five students from the Student Body. The analyses were run by the software Alceste. A total of 62 students participated in the research. For the discussion of political education, social movement and student bodies, the main theoreticians were studied, Freire, Gohn, Dayrell, Melucci, among others. The study revealed that the student bodies serve as learning space in the political context or for citizenship, and contribute for the strengthening of the school management. Although the existence of student bodies is legitimated, difficulties were pointed out in its recognition and organization. Students struggle to strengthen the entity and lack theoretical and organizational support. Even with the participation in the Program, the perceptions presented by the students demonstrate that the school does not seem to provide the necessary support to student participation and, therefore, it does not seem to accomplish the ProEMI’s goals related to the researched macro-field.